BUILDABILITY PROBLEMS IN CONSTRUCTION PROJECTS IN NIGERIA; CAUSES AND IMPACTS - Aina, Omotayo Olugbenga (European Scientific Journal, ESJ, 2015)
Adoption of buildability concepts has contributed to improved project delivery processes in the U. K, US and other countries. However, in Nigeria, the neglect of this concept shown by the preference accorded the traditional separation of design and construction has created fertile grounds for occurrence of buildability problems with its attendant effects. Determination of the causes of these problems in construction projects and their impact were the goals of this research. The study was conducted with questionnaire administered on sixty project managers of on-going building projects in Lagos, Nigeria. The respondents were required to evaluate causes of buildability problems in construction projects on a five- point likert scale and acted as a panel for analytical hierarchical process (AHP) for assessing impact of identified causes on the construction process. Findings revealed that the prominent causes of buildability problems were insufficient data and project drawing information, poor specification and choice of materials and inadequate project scope definition. Ranking of the AHP vectors revealed that impact of buildability problems on project delivery were mainly felt as inability of clients to get value for money spent, poor serviceability, functionality and structural instability and high component failure and high risk in building usage. These findings corroborated the culpability of the gulf between design and construction as the main cause of buildability problems and increased cost to clients.